STRATEGI PENGEMBANGAN KOMPETENSI PROFESIONAL GURU DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN DI MADARASAH ALIYAH NU SUNAN AMPEL PASURUAN - Futika Permatasari; Nia Agus Lestari; Chitra Dewi Yulia Christie (Prodi PAI STIT Sunan Giri Bima, 2023)
The purpose of this study was to determine the strategy of developing professional competence of teachers at Madrasah Aliyah NU Sunan Ampel Beji District, Pasuruan Regency. This research used descriptive method with qualitative approach. This research was conducted at Madrasah Aliyah NU Sunan Ampel Beji District, Pasuruan Regency. The data sources in this study were the Principal and teachers at Madrasah Aliyah NU Sunan Ampel Beji District, Pasuruan Regency. Data collection techniques in this study through interviews and field observations. While data analysis uses Miles and Hubberman analysis techniques, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study found that there are several strategies carried out to develop teachers' professional competence, namely 1) actively fostering teachers; 2) maximizing MGMP deliberations; 3) delegating teachers to attend various trainings; 4) applying discipline to educators and education personnel.